Trend and status of out-of-pocket payments for healthcare in Iran: equity and catastrophic effect - Satar Rezaei; Abraha Woldemichael; Mohammad Ebrahimi; Sina Ahmadi (SpringerOpen, 2020)
Abstract Background Equity in the distribution of health care resources and mitigating the risk of out-of-pocket (OOP) catastrophic healthcare expenditures (CHE) are the major objectives of the health system of a country. This study aims to measure equity in OOP payments for healthcare and the incidence of CHE among Iranian households over time. Methods This retrospective cross-sectional study utilized data extracted from the household income and expenditure survey (HIES) of Iran, collected by the Statistical Center of Iran. The analysis included a total of 174,341 households' five yearly data of 6 years starting from 1991 to 2017. Kakwani progressivity index (KPI) was used to measure the equity in OOP payment for each year and examine the households' incidence of CHE at 20%, 30%, and 40% of their capacities to pay (CTP). The trend series regression analysis was used to examine the trend in the KPI and the incidence of the CHE over time. Results The findings indicated that the households' expenditure on health out of their monthly budgets for the years 1991 and 2017 were 2.1% and 10.1%, respectively. The KPI for the OOP payment was negative for all 6-year observations (1991 = − 0.680; 1996 = − 0.608; 2001 = − 0.554; 2006 = − 0.265; 2011 = − 0.225, and 2017 = − 0.207), indicating that the OOP payments for healthcare are regressive and more concentrated among the socioeconomically disadvantaged households. There was a statistically significant (p = 0.003) increase in the KPI (i.e., decline in the regressivity) over time. The incidence of the CHE (1.12, 1.93, and 3.71%) in 1991 at the CTP levels of 20%, 30%, and 40% was lower than the incidence at the corresponding levels of CTP (5.26, 10.88, and 22.16) in 2017. The findings of the time-series regression indicated a statistically significant (p < 0.05) increase in the incidence of the CHE at the 20%, 30%, and 40% levels of the households' CTP. Conclusions The current study demonstrated that OOP payment as a source of healthcare funding in Iran is inequitable. While the use of interventions such as the prepaid and publicly funded programs may contribute to the reduction of CHE and improvement of equity in healthcare financing, further inequality analyses in the incidence of the CHE among households and its main determinants can contribute to evidence-informed planning to reduce the CHE in the context.